Juridical Analysis of Used Medical Device Import Regulations in Indonesia - G.Hutagalung; H.Sinaga (The Medical Journal of Hospital Management and Health Law, 2026)
This study examines the legal framework governing the importation of used medical devices in Indonesia, balancing healthcare accessibility with public safety. The introduction highlights the dilemma faced by developing nations regarding cost-effective healthcare solutions versus the risks of substandard medical equipment. The methods utilize a normative legal research approach, analyzing primary and secondary legal sources, including statutory regulations and judicial frameworks. The results indicate that while Indonesian law strictly regulates the import of second-hand goods to protect public health, certain regulatory ambiguities and enforcement gaps persist, particularly regarding exceptions for essential medical technology. The discussion delves into the literature review and comparative legal structures, demonstrating a significant research gap in how specific administrative guidelines align with overarching consumer protection and healthcare laws. It analyzes the tension between economic feasibility for local healthcare providers and the constitutional right to health safety. The conclusions suggest that the current regulatory framework requires harmonization, and the study offers concrete recommendations for legislative updates to establish clearer certification standards and stricter oversight mechanisms.